Dental students’ attitude toward underserved, a survey of an Iranian dental school - Zahra Yaghoubi (Journal of Medical Education Development)
Background & Objective: It is essential to cultivate dentists who are not only technically proficient but also socially sensitive in order to reduce oral health disparities. Assessing attitudes has been emphasized in dental education within this context. This study aimed to assess dental students' attitudes toward less privileged populations. Material & Methods: This cross-sectional study utilized the valid Persian version of the “Dental Student Attitude Toward Underserved Population” (DSATU) questionnaire to evaluate the attitudes of first and final year dental students at Mashhad dental school toward deprived populations. The questionnaire consists of 21 Likert scale questions across four domains addressing social expectations, student responsibility, personal efficacy, and access to care. The outcome variables were the overall and domain-specific scores of the DSATU questionnaire. Independent variables included students' gender and academic year. Statistical analysis was performed using SPSS version 22. Results: The questionnaire was administered to 52 first-year and 58 final-year students, yielding a response rate of 90%. The majority of participants were final-year students (55.7%) and female (59.6%). First-year students generally exhibited a more positive perspective, scoring 8 points higher than final-year students in the total survey: 85.53 (81%) versus 76.66 (73%) out of a maximum of 105 points. The decline in attitudes among final-year students was statistically significant in total and all domain scores (p < 0.05). There was no statistically significant gender difference in total DSATU and subdomain scores, except for access to care (p = 0.037). Conclusion: This study suggests less favorable attitudes toward underserved populations among final-year students. Longitudinal rigorous evaluation of students' attitudes provides better insights into the effectiveness of dental education.